The Influence of Cultural Context on the Interpretation and Implementation of Sustainable Development Goals in EFL Education - Thamer, Sanar M. (PT FORMOSA CENDEKIA GLOBAL, 2025)
The present research sought to explore the influence of cultural context on the interpretation and implementation of sustainable development goals in EFL education. The research followed the descriptive analytical method of research. (200) university students responded to a questionnaire of (24) items distributed over four dimensions. The results of the data analysis indicated that strong agreement among most of the respondents about the cultural contexts influence on the integration of sustainable development goals in Education (mean= 77%), ensuring that culture has a significant impact in how sustainability topics are perceived and discussed. Based on these results, the research concluded that while there are positive motivations and a high global awareness regarding sustainability-based education, there is a persistent need to respect and implement the students’ cultural and personal relevance in order to deepen the understanding and engagement of students